Improving Student Learning Outcomes through the Discovery Learning Model among Junior High School Students - Dalminah, Dalminah; Candra, Pasmah (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: Islamic education often faces challenges in engaging students and fostering deep understanding, especially when traditional teaching methods dominate the classroom. To address this, innovative learning models are required to make learning more student-centered and meaningful. Objective: This study aims to improve student learning outcomes using the Discovery Learning model in Islamic education. Method: A classroom action research (CAR) approach was employed at SMPN 01 Sungai Are in 2023, involving 26 first-grade students. Data was collected through tests and observations, and analyzed based on learning completeness scores. Result: The findings indicate that student learning outcomes improved progressively through Cycle I and Cycle II, demonstrating the effectiveness of the Discovery Learning model. Conclusion: The study confirms that implementing the Discovery Learning model enhances student learning outcomes, making it a valuable approach in Islamic education. Contribution: These findings serve as enrichment material for religious teachers and schools, providing theoretical and practical insights. Additionally, they offer a reference for future researchers exploring the effectiveness of Discovery Learning in improving student performance.